Intraoperative breakage of Sachse’s knife blade: a rare complication of optical internal urethrotomy (one case managing experience) - Kanodia,Gautam Kumar (2017)
ABSTRACT Optical internal urethrotomy (OIU) is the most common procedure performed for short segment bulbar urethral stricture worldwide. This procedure most commonly performed using Sachse’s cold knife. Various perioperative complications of internal urethrotomy have been described in literature including bleeding, urinary tract infection, extravasation of fluid, incontinence, impotence, and recurrence of stricture. Here we report a unique complication of breakage of Sachse knife blade intraoperatively and its endoscopic management.